(untitled) (Cardiovascular Journal, 2017)
Background: Aim of our study was to predict the effect of mitral valve leaflets excursion on mitral valve area following percutaneous transvenous mitral commissurotomy PTMC in patients of mitral stenosis. Methods: Total 70 patients with severe mitral stenosis who underwent PTMC were enrolled in the study.Transthoracic echocardiography was done the day before PTMC and 24-48 hours after PTMC. Mitral valve area, anterior and posterior leaflets excursion were recorded. The relation between leaftlet excursion and mitral valve after PTMC was evaluated. Results: Following PTMC there were significant increasein anterior leaflet excursion from 1.9 ± 0.2 to 2.3 ± 0.2cm (p<0.001), posterior leaflet excursion from 1.6±0.2to1.9 ± 0.2cm (p<0.001). Mitral valve areas increased from 0.8 ± 0.1 to1.7 ± 0.2cm²(p<0.001). Both leaflet excursion increased significantly with the increase in mitral valve area till the area reached a value of about 1.5 cm2, after which any further increase in mitral valve area was not associated with any further increase in leaflet excursion. Conclusion: PTMC is associated with immediate significant changes in mitral valve morphology in terms of splitting of fused mitral commissures, increased leaflets excursion and splitting of the subvalvular structures. Post PTMC leaflet excursion increases significantly with the increase in mitral valve area till the area reaches a value of about 1.5 cm2 after which any further increase in mitral valve area is not associated with any further increase in leaflet excursion. Cardiovasc. j. 2017; 10(1): 3-7